(untitled) (MAUSAM, 2024)
The track, intensity, and associated hazards of a cyclone are mostly pre- dicted using NWP models, satellites, and radar. Though the cyclones originate and strengthen in the ocean, they cause devastation in the populated land area over which they ultimately pass. Over the years, the accuracy of cyclone prediction has improved a lot. Yet, there is some uncertainty in the accurate prediction of track, intensity and associated hazards. In this article, we have studied super cyclone AMPHAN and its hazards for Kolkata, India. Here, we have proposed a new scheme for improving the forecast accuracy for cyclone distance, associated wind, and hazard for lead time up to 12-24 hours ahead based on curve fitting techniques and extrapolation using surface observational data. For the prediction of distance of the system from the concerned station and corresponding gusty wind speed, the accuracy of the proposed scheme is found to be better than the existing operational forecast and various reputed NWP models.